602 Using Plastic Surgery Techniques in Abdominal Wall Surgery. (19th August 2022) - Lee-A-Ping, K; Chintapatla, S; Chitsabesan, P; Lim, P; MacLeod, T
Abstract: Complex Abdominal Wall Hernias (CAWH) present a huge challenge to surgeons and patients often requiring Abdominal Wall Reconstruction (AWR). AWR aims to restore abdominal wall anatomy, improve function, and reduce the risk of future herniation. Plastic surgery techniques can be used including primary closure, skin grafts, flaps, tissue expansion and small bite, small stitch technique. Below are two cases where some of these techniques were utilised. Case 1: LC is a 65 y/o female with CAWH. Her gastric band became infected requiring a laparotomy for perforation of gastroesophageal junction. She subsequently had primary open repair of abdominal hernia using Permacol. It became infected requiring 5 debridements and application of a VAC device. Her hernia was a Ventral Hernia Working Group (VHWG) grade 3 at 10cm×16cm. Her CAWH was repaired using a Rives-Stoppa technique and a Surgimend mesh. The epigastric component of her wound was closed using a superiorly based local rhomboid flap and a Prevena VAC dressing. Case 2: KH is a 37 y/o female with a para-ileal conduit skin granuloma that was painful and refractory to other treatments such as silver nitrate and steroid topical treatments. She had excision of the area of granulation and her wound was closed using a local advancement flap taking account of previous scars raised and a prevena VAC dressing. Discussion: CAWH requiring AWR is a complex operation benefiting from plastic surgical specialists. Plastic surgical techniques can help with closure of the abdominal wall and reduce complication rates including wound infections and incisional hernia.